Influencing factors on compliance of timely visits among patients with proliferative diabetic retinopathy in southern China: a qualitative study. Issue 3 (27th March 2017) - Duan, Fang; Liu, Yuhong; Chen, Xiang; Congdon, Nathan; Zhang, Jian; Chen, Qianyun; Chen, Lingling; Chen, Xi; Zhang, Xiulan; Yu, Chengpu; Liu, Yizhi
Abstract : Objective: To identify the reasons for low adherence among patients with diabetic retinopathy (DR) in southern China using a qualitative method. Methods: Exploratory indepth interviews were conducted in 27 diabetic patients with proliferative diabetic retinopathy who required vitrectomy surgery at Zhongshan Ophthalmic Centre, Sun Yat-sen University, from March to August 2015. Qualitative data analysis and research software (ATLAS.ti7) was used for data processing and analysis. Results: Factors influencing the occurrence of timely visits included lack of DR related knowledge, fear and worries about insulin, interactions between patients and society combined with the complexity of emotions and social culture, and the economic burden of treatment. Conclusions: Although the reasons for low adherence involved social, emotional, cultural and economic factors, the key issue was the lack of awareness and knowledge of DR. Our findings have several practical implications for health policymakers and programme planners in China.